Occupational exposure to magnetic fields in case-referent studies of neurodegenerative diseases - Noonan, Curtis W.; Reif, John S.; Yost, Michael; Touchstone, Jennifer (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'Case-referent studies of Alzheimer`s disease, amyotrophic lateral sclerosis, and Parkinson`s disease were conducted to explore the relationship between these neurodegenerative diseases and occupational exposure to magnetic fields. Three methods of exposure assessment were used for the comparison, and the consistency of findings between these approaches was evaluated. ' ' METHODS ': 'Separate case-referent sets were formed from among recorded deaths of males in the state of Colorado for the years 1987 through 1996. The following three methods of exposure assessment were used: a dichotomous grouping of electrical versus nonelectrical occupations, a three-tiered grouping of potential magnetic-field exposure based on a combination of job title and industry, and categories of exposure based on the means of the magnetic fields estimated from a job-exposure matrix. ' ' RESULTS ': 'A positive association was observed for Parkinson`s disease with all the methods of magnetic-field exposure assessment, the odds ratio (OR) for the highest category in the job-exposure matrix being 1.50 [95% confidence interval (95% CI) 1.02-2.19]. Amyotrophic lateral sclerosis was associated with a history of electrical occupations (OR 2.30, 95% CI 1.29-4.09) but not with magnetic-field exposure as estimated by the job-exposure matrix. No consistent associations with magnetic fields were observed for Alzheimer`s disease. ' ' CONCLUSIONS ': 'This study provides some support for an association between occupational magnetic-field exposure and Parkinson`s disease, but the findings are novel and require replication. Associations with the other neurodegenerative diseases were inconsistent and dependent on the method of exposure assessment.
Keywords: Alzheimer’s disease; amyotrophic lateral sclerosis; case-referent study; electrical occupation; job-exposure matrix; magnetic fields; neurodegenerative disease; occupational exposure; Parkinson’s disease